Psychrophilic Lipase from Arctic Bacterium - Ramle, Zakiah (Trop Life Sci Res, 2016)
A lipase producer psychrophilic microorganism isolated from Arctic sample was studied. The genomic DNA of the isolate was extracted using modified CTAB method. Identification of the isolate by morphological and 16S rRNA sequence analysis revealed that the isolate is closely related to Arthrobacter gangotriensis (97% similarity). A. gangotriensis was determined as positive lipase producer based on the plate screening using specific and sensitive plate assay of Rhodamine B. The PCR result using Arthrobacter sp.’s full lipase gene sequence as the template primers emphasised a possible lipase gene at 900 bp band size. The gene is further cloned in a suitable vector system for expression of lipase.